The 9‐Borataphenanthrene Anion. (7th May 2020) - Bartholome, Tyler A.; Kaur, Aishvaryadeep; Wilson, David J. D.; Dutton, Jason L.; Martin, Caleb D.
Abstract: The 9‐borataphenanthrene anion is easily accessed by deprotonation of a 9, 10‐dihydro‐9‐boraphenanthrene and its diverse reactivity is investigated. Alkylation occurs at the carbon atom adjacent to boron, and room temperature hydroboration occurs across the B=C bond. The π‐manifold of the central BC5 ring coordinates to chromium in an η 6 fashion while only the B=C unit binds η 2 to gold, indicating versatility of the 9‐borataphenanthrene anion as a ligand. Supporting calculations rationalize the reactivity and aromaticity is corroborated by nucleus‐independent chemical shift (NICS) indices. Abstract : The 9‐borataphenanthrene anion is prepared which exhibits surprisingly diverse reactivity. Reactions with metal precursors revealed η 2 or η 6 coordination modes of the anion to the metal while the B=C carbon is alkylated upon reaction with methyl iodide. Pinacolborane adds the H−B unit across the B=C bond to generate a unique hydroboration products.